Effects of Rosehip Feed Supplementation on Egg Quality Parameters, Yolk Lipid Oxidation, and Blood Parameters of Laying Hens - Svetlana Grigorova; Natasha Gjorgovska; Vesna Levkov (Islamic Azad Univerty, Rasht Branch, Rasht, Iran, 2021)
The current study was conducted to evaluate the influence of rosehip supplementation on egg production, egg morphological characteristics, yolk lipid oxidation, and some blood parameters of laying hens. The experiment was carried out with a total of forty laying hens Lohmann classic brown breed, which randomly divided in two groups-control and experimental (20 hens in each group). The diet of experimental hens was supplemented with 0.5% dried and milled fruits of rosehip. The trial lasted 50 days. Rosehip fruits supple-mentation to the layers diet for 40 days had no significant effect on their final live body weight, egg produc-tivity, and egg morphological characteristics during the experimental period. However, the triglycerides level in the blood serum as well as yolk malondialdehyde (MDA) level significantly decreased during egg storage 30 days in the fridge (P<0.05), and during 30 days on room temperature (P<0.01). The use of 0.5% rosehip fruits led to a significant increase in egg yolk pigmentation (P<0.001).
Keywords: MDA level, poultry, Rosa canina, yolk pigmentation